The The Relationship Between Family Social Support And Adversity Quotient With Psychological Readiness of Internship Students In The Era Of The Independent Curriculum At Public High Schools In Surabaya - Febry, Ollyvia; Suryanto, Suryanto; Santi, Dyan Evita (Yayasan Minang Darussalam, 2023)
One of the implementations of the Merdeka Curriculum in Vocational High Schools is developed through internships or work practices. The internship can run well if students have readiness, especially psychological readiness. The purpose of this study is to analyze how the relationship is formed between family social support, adversity quotient, and psychological readiness in Apprenticeship students in the Independent Curriculum era, while the research hypothesis is that there is a partial or simultaneous relationship between family social support, adversity quotient, and psychological readiness in Apprenticeship students in the Independent Curriculum era. This research is a type of quantitative research with Multiple Linear Regression techniques, where the sample size is 440 public vocational high school students in Surabaya City, taken randomly from 10 public vocational schools through the Simple Random Sampling technique. The results of this study indicate that family social support has a positive and significant relationship with psychological readiness. Adversity quotient has a positive and significant relationship with psychological readiness. Furthermore, family social support and adversity quotient simultaneously have a positive and significant relationship with psychological readiness. Vocational High School students need full support, especially from their families (family social support) in facing internship activities, besides that they must have the intelligence to solve the problems faced (adversity quotient) so that they do not give up easily and are discouraged in carrying out internship activities, so as to form mental readiness through improving personal quality, intellectual values, motivation, emotional, and professionalism in Vocational High School students in Surabaya.